Determination of Zoning Recharge Area and Spring Conservation in the Upstream Sub-Basin of the Jali River, Gebang District, Purworejo Regency, Central Java Province - Mia Fitri Aurilia; Dian Hudawan Santoso; Andi Sungkowo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2021)
Human needs for clean water can be obtained from various sources, one of those is springs. The spring is the main water source for the people in Redinkidul Hamlet. The dependence of the community on springs shows that there is a need for conservation of spring recharge areas. The purpose of this study was to determine the ability of recharge areas to absorb water and provide conservation direction for spring recharge areas. The research method used is survey and mapping methods to obtain data on existing conditions in the field, scoring and overlay methods to determine the condition of the recharge area based on the results obtained. The scoring parameter refers to Permen PU No. 2 of 2013. The results obtained show that the spring recharge area zone has a moderate class with a score of 11-13. The highest score obtained is on the parameters of land use and rainfall. Based on these results, the proposed conservation directives are in the form of technical conservation directions in the form of bund terraces and spring support buildings. This conservation is needed so that the potential of the spring is maintained.